The Association of Body Mass Index With the Risk of Pulmonary Hypertension in Adults: A Systematic Review and Meta-Analysis of Observational Studies - Pu, Shoufang; Yin, Lidan; Wen, Bi; He, Juan (Frontiers in Medicine, 2022)
Backgrounds Findings regarding the association of body mass index (BMI) with pulmonary hypertension (PH) are conflicting, and there is no systematic review and meta-analysis to summarize the results. Therefore, the purpose of this systematic review and meta-analysis is to assess this relationship. Methods To detect the relevant articles, PubMed, Scopus, and Google Scholar were searched until February 2021. Included essays were pooled using a random-effect model. Cochrane Q-test and I2-test was applied to assess between-study heterogeneity. Results Fourteen articles (eight cross-sectional and four cohort studies) were included in the meta-analysis. The meta-analysis of comparing highest vs. lowest BMI categories did not indicate a significant association between BMI and PH (Summary Effect Estimate: 1.59 (95% CI: 0.50, 5.07, I2 = 92.3). Furthermore, The summary risk estimate for a one-unit increment in BMI was 1.01 (95 % CI: 0.99, 1.03), with high heterogeneity, I2 = 73.5 %, P heterogeneity <0.001). Subgroup analysis showed significant positive association between BMI and the risk of PH in studies controlled for cofounders, and studies with higher sample sizes (≥2,000). Conclusion There is no significant association between BMI and risk of pulmonary hypertension. Further studies are required to confirm these findings.